2015
DOI: 10.1089/jir.2014.0237
|View full text |Cite
|
Sign up to set email alerts
|

Hyporeactivity of Alveolar Macrophages and Higher Respiratory Cell Permissivity Characterize DBA/2J Mice Infected by Influenza A Virus

Abstract: Influenza A virus remains a major public health problem. Mouse models have been widely used to study influenza infection in mammals. DBA/2J and C57BL/6J represent extremes in terms of susceptibility to influenza A infection among inbred laboratory mouse strains. Several studies focused specifically on the factors responsible for the susceptibility of DBA/2J or the resistance of C57BL/6J and resulted in impressive lists of candidate genes or factors over- or underexpressed in one of the strains. We adopted a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, this phenotype was not associated with a higher viral load; in fact, the HA190 mutant and the double mutant showed the lowest virus titers in mouse lungs. This effect may be explained by an enhanced inflammatory response that impairs virus replication and, in the case of the HA190ϩHA212 mutant, results in increased pathogenicity (52)(53)(54). The murine airway epithelium is known to contain predominantly ␣2,3-linked sialic acids (55).…”
Section: Discussionmentioning
confidence: 99%
“…However, this phenotype was not associated with a higher viral load; in fact, the HA190 mutant and the double mutant showed the lowest virus titers in mouse lungs. This effect may be explained by an enhanced inflammatory response that impairs virus replication and, in the case of the HA190ϩHA212 mutant, results in increased pathogenicity (52)(53)(54). The murine airway epithelium is known to contain predominantly ␣2,3-linked sialic acids (55).…”
Section: Discussionmentioning
confidence: 99%
“…In the alveolar space, the virus is picked up by alveolar macrophages and, together with intense phagocytic activity, it generates a swift inflammatory response. 2,12 Through immunohistochemical staining, experimental infections in mice and pigs have shown that viral antigens are mainly detected in the epithelium of the airways and in alveolar macrophages, which have presented systematically higher immunoreactivity. [12][13][14] Through IHC, we detected positivity towards infection by SIV in a natural presentation of a field virus, by using this technique as a rapid tool with in situ precision and reduced costs for the detection of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…2,12 Through immunohistochemical staining, experimental infections in mice and pigs have shown that viral antigens are mainly detected in the epithelium of the airways and in alveolar macrophages, which have presented systematically higher immunoreactivity. [12][13][14] Through IHC, we detected positivity towards infection by SIV in a natural presentation of a field virus, by using this technique as a rapid tool with in situ precision and reduced costs for the detection of this disease. Additionally, Capuccio 15 evidenced differences between the intensity and distribution of the viral antigen in the lungs depending on which SIV strain was present and on the stage of infection, suggesting a new approach for greater precision in the etiological diagnosis of SIV that would complement molecular techniques with IHC.…”
Section: Discussionmentioning
confidence: 99%
“…injection of Ketamine (80 mg/kg) and Xylazine (10 mg/kg). Frozen virus aliquots were thawed, centrifuged for 5 min at 2,500 g, washed and diluted to a non-lethal dose in C57BL6 strain [9 plaque forming unit (pfu)] in sterile DPBS ( 31 ). For infection, 30 μl of H1N1 virus or DPBS were inoculated via i.n.…”
Section: Animals and Methodsmentioning
confidence: 99%